On Paired Double Domination Number of Grid Graphs - V. Anusuya, M. N. Sree Valli (Mathematical Statistician and Engineering Applications, 2022)
A Paired-dominating set of a graph G is a dominating set of vertices whose induced sub graph has a perfect matching and a double dominating set is a dominating set that dominates every vertex of G at least twice. A Paired-double dominating set of a graph G is a double dominating set of vertices whose induced sub graph has a perfect matching. In this paper, we characterize the Paired double domination number of the Cartesian product of path graphs. We determine the Paired double domination numbers of , where n is even and